2015
DOI: 10.1002/ange.201503935
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Hydrogen Production by an Aluminum(III) Complex: Ligand‐Based Proton and Electron Transfer

Abstract: Environmentally sustainable hydrogen‐evolving electrocatalysts are key in a renewable fuel economy, and ligand‐based proton and electron transfer could circumvent the need for precious metal ions in electrocatalytic H2 production. Herein, we show that electrocatalytic generation of H2 by a redox‐active ligand complex of Al3+ occurs at −1.16 V vs. SCE (500 mV overpotential).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…5 For example, Berben et al showed that bis(imino)pyridine complex of aluminum catalyzed the dehydrogenative coupling of benzylamine, 6 dehydrogenation of formic acid, 7 and electrocatalytic production of hydrogen via a metal-ligand cooperative mechanism. 8 Roesky et al illustrated that the -diketiminato aluminum hydride complexes mediated the catalytic hydroboration of carbonyl compounds and alkynes. 9, 10 Thomas and Cowley et al reported that commercially available aluminum hydrides such as DIBAL-H and LiAlH 4 catalyzed the hydroboration of alkenes, alkynes, and nitriles via σ-bond metathesis.…”
Section: Introductionmentioning
confidence: 99%
“…5 For example, Berben et al showed that bis(imino)pyridine complex of aluminum catalyzed the dehydrogenative coupling of benzylamine, 6 dehydrogenation of formic acid, 7 and electrocatalytic production of hydrogen via a metal-ligand cooperative mechanism. 8 Roesky et al illustrated that the -diketiminato aluminum hydride complexes mediated the catalytic hydroboration of carbonyl compounds and alkynes. 9, 10 Thomas and Cowley et al reported that commercially available aluminum hydrides such as DIBAL-H and LiAlH 4 catalyzed the hydroboration of alkenes, alkynes, and nitriles via σ-bond metathesis.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] Recently our group has reported a diorgano diselenide derived from the o-aminodiselenide ligand, which could activate aerial oxygen towards the oxidation of organothiols. [36][37] Inspired by nature 38 and by the non-transition metal electrocatalysts; zinc thiosemicarbazone and aluminium-bis aminopyridine (Scheme 1) for hydrogen evolution reactions (HER) from water, [30][31][39][40] herein, we report the synthesis and structural characterization of the novel bimetallic zinc selenolate electrocatalyst 1 that catalyzes the water-splitting reaction by ligand assisted pathways in both directions; oxygen evolution and hydrogen evolution reactions without adding acid or base. Mechanistic insights into the electrocatalytic activity of bimetallic zinc selenolate complex have also been gained by synthesizing mercury selenolate catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Umehara, Kuwata, and Ikariya demonstrated cleavage of the NN bond of hydrazines with an Fe pincer complex that relies on the ability of the ligand to undergo redox changes through multiple reversible protonation events 11. Thompson and Berben demonstrated the electrocatalytic production of dihydrogen by a ligand‐based protonation approach 12. Relatedly, Kirchner and co‐workers demonstrated the heterolytic cleavage of dihydrogen with an Fe‐NNN pincer complex 13.…”
mentioning
confidence: 99%